EXPERT SYSTEM FOR DISEASE DIAGNOSIS IN SHALLOT PLANTS USING ANALYTICAL HIERARCHY PROCESS AND CERTAINTY FACTOR METHOD - Fitri, Sahdania; Sokid, Sokid; Iskandar, Iskandar (INTI TALAFA, 2025)
Shallots are an important agricultural commodity in Indonesia, but are often threatened by diseases that can harm farmers. To overcome this, this study developed an expert system to diagnose diseases in shallots quickly and accurately. This system combines two methods, namely the Analytical Hierarchy Process (AHP) and Certainty Factor (CF). The AHP method is used to determine the weight of disease symptoms based on their level of importance, which is then used in the CF calculation to calculate the level of certainty of the diagnosis. The combination of these two methods is expected to increase the accuracy of the diagnosis produced by the expert system. This system is implemented in a web-based platform. The tests carried out showed results that were in accordance with manual calculations. For example, the diagnosis of purple spot disease with the system obtained a result of 31% and manual calculations 31.34%, lanas disease with the system 13% and manual 13.1%, and powdery mildew disease with the system 29% and manual 29.4%. The only difference is in the rounding of the values. Based on the test results, this expert system was successful as expected and can be used by the community to diagnose diseases in shallots. Keywords: Expert System, Shallots, Analytical Hierarchy Process (AHP), Certainty Factor (CF), Disease Diagnosis.